2021
DOI: 10.1080/0015198x.2021.1874726
|View full text |Cite
|
Sign up to set email alerts
|

Equity Investing in the Age of Intangibles

Abstract: E xpenditures for the creation of intangible capital have increased since the 1990s, but accounting standards have not adapted to this increase. Among the sample of non-US companies we studied for this article, the proportion of capitalized intangible assets (excluding goodwill) relative to total assets increased from 0.2% to 2.2% between 1994 and 2018, and for US companies, these assets rose from 2.75% to 6.12%. Uncapitalized intangible capital expenditures, such as those on research and development (R&D), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Intuitively, intangible assets are more firm-specific and, thus, less comparable across firms than tangible assets (e.g., fixed assets, real estate, factories, and equipment). Compounding the difficulty, the existing accounting and reporting rules have not kept pace with the rise of intangible investments (Dugar & Pozharny, 2021 ), potentially leading to significant mismeasurement of important firm characteristics, such as productivity (Bhandari & McGrattan, 2021 ; Corrado et al, 2009 ; Haskel & Westlake, 2017 ), book equity and earnings (Lev, 2019 ; Srivastava, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitively, intangible assets are more firm-specific and, thus, less comparable across firms than tangible assets (e.g., fixed assets, real estate, factories, and equipment). Compounding the difficulty, the existing accounting and reporting rules have not kept pace with the rise of intangible investments (Dugar & Pozharny, 2021 ), potentially leading to significant mismeasurement of important firm characteristics, such as productivity (Bhandari & McGrattan, 2021 ; Corrado et al, 2009 ; Haskel & Westlake, 2017 ), book equity and earnings (Lev, 2019 ; Srivastava, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Palmon and Yezegel ( 2012 ) found that analysts’ recommendation revisions were more valuable for firms with high research & development (R&D) intensity, the hypothesis being that R&D intensity increases information asymmetry. Furthermore, Dugar and Pozharny ( 2021 ) found that the value relevance of book equity and earnings declined only in firms with high intangibles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors [9,20] consider methods for optimizing investments, as well as ways to optimize the total cost of attracting capital investments and argue that capital investments in fixed assets have an advantage over other types of investments.…”
Section: Problem Statementmentioning
confidence: 99%
“…Let G = (V, B i ) be a graph in which the ending V is a set of variables; B i is nonreflexive binary relation on [9,20]. Each variable v has a set of parent variables c(v) ⊆ V and a set of all d(v) ⊆ V descendants .…”
Section: Bayesian Networkmentioning
confidence: 99%
“…At the same time, it is necessary to ensure that the evaluation system can cover the corresponding costs and applications of the data assets. [9]. We calculate the main weights of different evaluation indicators and the corresponding target layer, design specific operation methods, and verify the operability of the evaluation system with examples [10].…”
Section: Introductionmentioning
confidence: 99%